2020
DOI: 10.3390/su12051818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Agglomeration Characteristics of Rural Settlements in Poor Mountainous Areas of Southwest China

Abstract: The rural settlements in poverty-stricken mountainous areas are the "living fossils" of an economic society with the characteristics of spatial dispersion and are slowly changing. Spatial agglomeration is the development direction of rural settlements. In-depth exploration of the spatial agglomeration characteristics and influencing factors of rural settlements in poverty-stricken mountainous areas is a way to provide a basis for rural settlement restructuring. We selected Pengshui County, a national poverty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…In general, the scales of residential land in plain areas are large, and the scales of residential land in mountainous areas are relatively small. Elevation and slope have greatly influenced the safety and convenience of residents′ living and production conditions [40]. Resource endowments include natural resources (light, temperature, cropland, etc.)…”
Section: An Explanatory Framework For Rural Residential Land Expansionmentioning
confidence: 99%
“…In general, the scales of residential land in plain areas are large, and the scales of residential land in mountainous areas are relatively small. Elevation and slope have greatly influenced the safety and convenience of residents′ living and production conditions [40]. Resource endowments include natural resources (light, temperature, cropland, etc.)…”
Section: An Explanatory Framework For Rural Residential Land Expansionmentioning
confidence: 99%
“…It is undeniable, however, that cultivated land, towns, and population density factors are the most important in Inner Mongolia. Numerous studies have shown that, in traditional farming societies, cultivated land is the basic guarantee for rural development, and villages are distributed close to cultivated land [ 16 , 17 ]. This is the case in Inner Mongolia, which is a large agricultural province, and the importance of cultivated land is irreplaceable.…”
Section: Discussionmentioning
confidence: 99%
“…Rural settlements are the regional carriers of natural, economic, and social composite systems [ 14 16 ]. Spatial distribution and agglomeration of rural settlements on different scales and landforms have obvious regional differences [ 2 , 17 ]. In China, rural settlements show an overall low degree of agglomeration, small scale, and large regional variation [ 1 , 2 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural conditions are the most important factor, among which elevation is most commonly considered to be a basic natural environmental factor that affects the distribution of rural settlements [ 42 , 43 , 44 ]. Luo et al [ 45 ] found that nearly 80% of rural settlements were gathered with a slope of 6~25°, while the elevation had a higher significant agglomeration effect on rural settlements than slope. Precipitation and temperature were positively related in arid regions, while there was no apparent correlation in Southeastern China [ 46 ].…”
Section: Literature Reviewmentioning
confidence: 99%